The comparative sustainable development in Sub-Saharan Africa - Simplice Asongu (African Governance and Development Institute (AGDI), 2017)
Motivated by sustainable development challenges in Sub-Saharan Africa, this study assesses the comparative persistence of environmental unsustainability in a sample of 44 countries in the sub-region for the period 2000 to 2012. The empirical evidence is based on Generalised Method of Moments. Of the six hypotheses tested, it is not feasible to assess the hypothesis on resource-wealth because of issues in degrees of freedom. As for the remaining hypotheses, the following findings are established. (i) Hypothesis 1 postulating that middle income countries have a lower level of persistence in carbon dioxide (CO2) emissions is valid for CO2 per capita emissions, CO2 emissions from electricity and heat production and CO2 emissions from liquid fuel consumption. (ii) Hypothesis 2 on the edge of French civil law countries is valid for CO2 emissions from liquid fuel consumption and CO2 intensity, but not for CO2 per capita emissions. (iii) Hypothesis 3 on the postulation that politically-unstable countries reflect more persistence is valid for CO2 per capita emissions. (iv) Hypothesis 5 on the propensity for landlocked countries to be associated with more persistence in CO2 emissions is valid for CO2 per capita emissions but not for CO2 emissions from liquid fuel consumption. (v) Hypothesis 6 maintaining that Christianity-dominated countries are more environmentally friendly with regard to CO2 emissions is valid for CO2 per capita emissions but not for CO2 emissions from liquid fuel consumption and CO2 intensity. Implications for policy and theory are discussed.
Keywords: C52; O38; O40; O55; P37; 330; CO2 emissions; Sustainable development; Environment; Africa